2018
DOI: 10.11648/j.ejpm.20180601.15
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Underlying Problems of Eradication of Poliomyelitis in the Remaining Endemic Countries

Abstract: In 1988, the World Health Assembly of the World Health Organization (WHO) launched the Global Polio Eradication Initiative (GPEI), with the resolve to interrupt transmission of wild poliovirus (WPV) worldwide by the year 2000.Eighteen years after the intended year of eradication, that target is yet to be achieved. To investigate the reasons behind this, a check of recent publications on poliomyelitis and polio virus was carried out. The databases and websites of institutions and organizations involved in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Many studies have demonstrated that increased risk perception of the virus is a decisive predictor variable for COVID-19 Vaccine acceptance (Guidry et al, 2021;Lin et al, 2021;Shektar et al, 2021;Dzieciolowska et al, 2021). On the other hand, the high vaccine hesitancy in Northern Nigeria may be related to cultural and religious patterns, which was demonstrated in the past with cases of mass refusal and boycott of the polio vaccination program that led to the resurgence in the diseases and beyond (Ike et al, 2018;Nzaji et al, 2020;Tobin et al, 2021;Adebisi et al, 2021). Moreover, the relatively lower figures for the burden of the pandemic in the Northern states of Nigeria could explain the high hesitancy (Hassan et al, 2020).…”
Section: The Main Findings In Briefmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that increased risk perception of the virus is a decisive predictor variable for COVID-19 Vaccine acceptance (Guidry et al, 2021;Lin et al, 2021;Shektar et al, 2021;Dzieciolowska et al, 2021). On the other hand, the high vaccine hesitancy in Northern Nigeria may be related to cultural and religious patterns, which was demonstrated in the past with cases of mass refusal and boycott of the polio vaccination program that led to the resurgence in the diseases and beyond (Ike et al, 2018;Nzaji et al, 2020;Tobin et al, 2021;Adebisi et al, 2021). Moreover, the relatively lower figures for the burden of the pandemic in the Northern states of Nigeria could explain the high hesitancy (Hassan et al, 2020).…”
Section: The Main Findings In Briefmentioning
confidence: 99%
“…Disturbingly, Nigeria once experienced a striking example of widespread vaccine refusal. This incident occurred in 2003–2004 when northern Nigeria boycotted the polio immunization program, which caused the disease to reemerge in the nation and beyond (Adebisi et al ., 2021; Ike et al ., 2018; Kabamba Nzaji et al ., 2020; Tobin et al ., 2021). LMIC residents may not be aware of the risks associated with the disease; hence, they may be less eager to undergo vaccinations as a result, given that COVID-19 mortality rates in LMICs have consistently been lower than those in higher-income nations (Brown et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%